Varitions in Body Weigh and Bony Length of the Fetus Rattus Norvegicus Albino Wistar Stain Given Coffee With Increased Levels - Armaita Armaita; Yessy Aprihatin; Erfita Yanti; Aulia Asman; Linda Marni (Pascasarjana, Universitas Negeri Padang, 2020)
The fetus gets everything it needs through the bloodstream including nutrition, oxygenation, if it is blocked the fetus will lack all that is needed for growth and development. As a result, the narrowing of the blood vessels may be able to result in impaired growth and developmental disorders can occur. The caffeine in coffee during pregnancy crosses the placenta and reaches the baby, thereby reducing blood flow to the placenta, thus endangering the baby. Food and drag administration in 1980, found that caffeine crosses the brain and blood barrier and it is thought that the fetus may not have the enzymes needed to detoxify itself from caffeine through a process known as demethylation. Some scientists also try to determine how caffeine interferes with cell growth and fetal development. Various epidemiological studies show that there is a strong relationship of the effects of caffeine. The risk of miscarriage in pregnant women who consume a cup or more of coffee per day was shown in a 1998 study. Other studies have shown that coffee can cause weight loss in babies for children and also an increased rate of abortion spontaneous. This type of research is an experiment with a post test only control group design research design that is a design used to measure the effect of treatment in the experimental group by comparing treatment results with the control group ending the treatment period. The study was conducted at the Anatomy Stikes Cup of Sakti Pariaman Cup. The extraction was carried out in the L2DIKTI SUMBAR RIAU JAMBI Laboratory. This research was conducted from March-November 2019. The total number of mice during the study were 32 individuals. The results of this study were tabulated data and analyzed data using SPSS 2007 with the Anova test of 95% confidence level. From the Anova test results it was found that there was a significant relationship between caffeine on body weight and fetal body length of experimental animals with a p value of 0.00.